PENERAPAN METODE INQUIRY UNTUK MENINGKATKAN KEAKTIFAN SISWA KELAS X DI SMK KARYA GUNA 1 BEKASI - Adrian Syahrajad Hirar; Laela Apri Liani (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Islamic religious education as a business process that contains uniqueness and characteristics, namely activating, increasing and strengthening norms, believe me, that is the spiritual-spiritual foundation of a person, in his attitude and behavior, his behavior is manifested in accordance with the rules. Religion I believe that human values ​​are behaviors that express the whole person, both externally and spiritually, and are the underlying drivers of behavior. Education is an absolute process of maturing through information and training in various skills and values ​​related to life activities that are in accordance with educational goals. Namely increasing the nation's intelligence and developing the Indonesian people as a whole, namely people who believe in and fear God Almighty. As well as creating human beings who are honest, healthy, knowledgeable and responsible. The inquiry method is a series of learning activities that emphasize critical thinking and analysis to find an answer. The thinking process occurs with the process of interaction between teachers and students. This method is also called the heuristic method, which comes from the Greek word found heuristic